2016
DOI: 10.1007/s10549-016-4013-7
|View full text |Cite
|
Sign up to set email alerts
|

miRpower: a web-tool to validate survival-associated miRNAs utilizing expression data from 2178 breast cancer patients

Abstract: In summary, we established an integrated platform capable to mine all available miRNA data to perform a survival analysis for the identification and validation of prognostic miRNA markers in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
632
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(645 citation statements)
references
References 31 publications
12
632
1
Order By: Relevance
“…However, this does not negate their potential cancer-related functions. In order to further explore the results, as an example, we performed survival analysis on four SDEmiRNAs unique to BRCA (absolute log2FC values > 1) by using miRpower [40]. Except hsa-mir-329–2 which is not in miRpower, the remaining three SDEmiRNAs suggest significant survival differences (log-rank p value < 0.01) between groups with under-/over-expression of each SDEmiRNA after optimizing the patient threshold (Figure S4): hsa-mir-4784 (Hazard Ratio (HR) = 1.82), hsa-mir-1262 (HR = 0.58), and hsa-mir-320c-1 (HR = 0.68).…”
Section: Resultsmentioning
confidence: 99%
“…However, this does not negate their potential cancer-related functions. In order to further explore the results, as an example, we performed survival analysis on four SDEmiRNAs unique to BRCA (absolute log2FC values > 1) by using miRpower [40]. Except hsa-mir-329–2 which is not in miRpower, the remaining three SDEmiRNAs suggest significant survival differences (log-rank p value < 0.01) between groups with under-/over-expression of each SDEmiRNA after optimizing the patient threshold (Figure S4): hsa-mir-4784 (Hazard Ratio (HR) = 1.82), hsa-mir-1262 (HR = 0.58), and hsa-mir-320c-1 (HR = 0.68).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to clinical and molecular heterogeneity in different studies, as well as methodological difference regarding to reproducibility and normalization, there exists a limitation to identify the specific miRNAs as potential diagnostic and prognostic markers [27]. In addition, the number of patients enrolled in each study is generally small.…”
Section: Discussionmentioning
confidence: 99%
“…Using miRpower 33 , we observed that lower expression of miR-29b-1 and miR-29a is associated with decreased relapse-free survival (RFS) in overall breast cancer and in patients with ER + primary tumors (Supplementary Fig. 9).…”
Section: Discussionmentioning
confidence: 99%